Implementasi Konvensi Hak-Hak Anak 1989 ( United Nations Convention On the Right of the Child ) Terhadap Pelanggaran Hak Asasi Anak Di Belarusia - Sinay, Susan Laura; Wattimena, Josina Augustina Yvonne; Noya, Ekberth Vallen (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Child protection is all efforts made to create conditions so that every child can exercise their rights and obligations for the proper development and growth of children physically, mentally and socially. Child protection is a manifestation of justice in a society, thus child protection is sought in various fields of state and social life. Child protection activities have legal consequences, both in relation to written and unwritten law The Convention of Rights of the Child was ratified by the United Nations General Assembly on November 20, 1989, and entered into force on September 2, 1990. The Convention on the Rights of the Child is an instrument that formulates universal principles and legal norms regarding the position of children. As such, the Convention on the Rights of the Child is an international human rights treaty that incorporates civil, political, economic and cultural rightsPurposes of the Research: Analyze and discuss the form of sanctions against perpetrators of violations of children's rights in Belarus and analyze and discuss the regulation of the protection of children's rights based on the 1989 United Nations Convention on the Rights of the Child.Methods of the Research: This type of research is normative juridical where the research is carried out by collecting primary, secondary and tertiary data obtained using literature studies. The data that has been collected is analyzed qualitatively in which the description is arranged systematically based on legal disciplines to achieve clarity of the problems to be discussed.Results / Findings / Novelty of the Research: The results of this study indicate that violations of children's rights in Belarus that have occurred have not been responded to properly, the State as an actor has not yet carried out its role and function as a protector of its citizens. The perpetrators of violations have not yet been prosecuted, therefore it is necessary to affirm human rights observers to continue to oversee violations of children's rights that occur in Belarus